Home » Aptitude » Algebra » Question
  1. Find the value of √(x² + y² + z)(x + y - 3z) ÷ ³√xy³z² when x = + 1, y = –3, z = – 1.
    1. 1
    2. 0
    3. –1
    4. 1
      2
Correct Option: C

Expression =
(x² + y² + z)(x + y - 3z)
= 1
³√xy³z²

Putting x = 1, y = –3, z = –1
Expression =
(1 + 9 - 1)(1 - 3 + 3)
= 1
³√ 1 × (-27) × 1

Expression =
3
= -1
-3

Note : Original question is :
(x² + y² + z)(x + y - 3z) ÷ ³√xy³z²
which gives answer = – √7 which is not in options.



Your comments will be displayed only after manual approval.